Ultrastructural study of the salivary glands of the sugarcane spittlebug Mahanarva fimbriolata (Stal, 1854) (Euhemiptera : Cercopidae) - Nunes, P. H.; Camargo-Mathias, M. I. (Elsevier B.V., 2006)
Spittlebugs are insects that suck sap from plants and regurgitate saliva containing toxic enzymes into the leaves. As a consequence, the conductive channels are blocked resulting in dry leaves, thus giving a burned aspect to the plantation. This work performed ultrastructural analyses of the salivary glands of the sugarcane spittlebug Mahanarva fimbriolata, since these organs produce the enzymes that are injected into the plants, thus being responsible for the economic losses in the production of sugarcane. Three kinds of secretory cells are found in principal gland, forming the lobules I-IV. The main differences among these cells relate to size, morphology and electron density of the secretory vesicles. The accessory glands contain different secretory vesicles to those in the principal gland. Muscular cells are found around the entire gland. The different secretory vesicles found in both principal and accessory glands indicate that the gland produces different substances or that the secretion in the interior of cells passes through a maturation process. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: spittlebug; sugarcane; Mahanarva fimbriolata; salivary gland